Association of uterine wall thickness with pregnancy outcome following uterine‐sparing surgery for diffuse uterine adenomyosis. (30th October 2015) - Otsubo, Yasuo; Nishida, Masato; Arai, Yuko; Ichikawa, Ryota; Taneichi, Akiyo; Sakanaka, Miyako
Abstract : Background: The risk of uterine rupture is a major concern for women who become pregnant after undergoing an adenomyomectomy. Aims: The aim of this study was to investigate the association of uterine wall thickness with pregnancy outcome. Materials and Methods: Uterine wall thickness was measured using sonography and/or magnetic resonance imaging in 23 pregnant women who underwent uterine‐sparing surgery for diffuse uterine adenomyosis prior to conception. Results: Of the 23 women, 10 (43.5%) had an early miscarriage and 13 (56.5%) proceeded to delivery. Of the ten early miscarriage cases, two had a uterine rupture caused by excision of the uterine wall to within 7 mm. Conclusions: Wall thickness of the excised uterus was highly associated with uterine rupture. We concluded that optimum wall thickness for conception and preventing uterine rupture during pregnancy may range from 9 to 15 mm.